The Triple Helix of innovation as a double game involving domestic and foreign actors - Mêgnigbêto Eustache (Journal of Data and Information Science, 2024)
The collaboration relationships between innovation actors at a geographic level may be considered as grouping two separate layers, the domestic and the foreign. At the level of each layer, the relationships and the actors involved constitute a Triple Helix game. The paper distinguished three levels of analysis: the global grouping together all actors, the domestic grouping together domestic actors, and the foreign related to only actors from partner countries.